VD_FINDINFO HC / 2024 / 518 vom 13. Juni 2024 - VD Tribunal cantonal (2024)
EXPERT, RÉCUSATION, FRAIS D'EXPERTISE, SUREXPERTISE, DOMMAGE IRRÉPARABLE, REJET DE LA DEMANDE | 183 al. 2 CPC (CH), 184 al. 3 CPC (CH), 319 let. b CPC (CH), 47 al. 1 let. f CPC (CH), 49 al. 1 CPC (CH), 50 al. 2 CPC (CH)